2009
DOI: 10.1590/s1020-49892009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels for the most frequent radiological examinations carried out in Brazil

Abstract: Objectives. A large-scale survey of doses to patients undergoing the most frequent radiological examinations was carried out in health services in São Paulo Conclusions. Despite the reduced number of ESD values and rooms for the pediatric patient group, it is recommended that practices in chest examinations be revised and that specific national reference doses and image quality be established after a broader survey is carried out.Thermoluminescent dosimetry, radiology, Brazil. ABSTRACTThe radiation protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(15 reference statements)
1
4
1
1
Order By: Relevance
“…In addition, in our study the exposure parameters in chest radiographies were higher, therefore, they are expected to have a higher ESDs. In our study, the ESD values for chest examination in both projections, PA and LAT, were higher than those of recommended by the UK (35) , Brazil (36) and Slovenia (37) . Owning to the results, women have a higher cancer probability risk in comparison to men.…”
Section: Discussioncontrasting
confidence: 73%
“…In addition, in our study the exposure parameters in chest radiographies were higher, therefore, they are expected to have a higher ESDs. In our study, the ESD values for chest examination in both projections, PA and LAT, were higher than those of recommended by the UK (35) , Brazil (36) and Slovenia (37) . Owning to the results, women have a higher cancer probability risk in comparison to men.…”
Section: Discussioncontrasting
confidence: 73%
“…The chest was selected because it is also one of the most common radiographic examinations performed in typical clinical practice [8,15,16] and appears to be the most commonly used anatomic area for studies examining dose optimization and/ or image quality [4,7,8,10,11,14,17,18]. The skull was selected because, although it is not a common radiographic examination in developed countries, it is still frequently performed in developing countries because of the prohibitive costs of computed tomography [19]; it is an area for which highquality examinations are required for diagnosis, especially in the event of nonaccidental injury and for which radiographs are generally of poor quality [20,21]; and it has been used in other studies examining dose optimization and/or image quality [13,21]. The hand was selected because it is a much thinner anatomic area than the other areas used in this study, and thus, changes in technical factors may affect image quality more prominently; also, this anatomic area does not appear to have been used in previous studies examining dose optimization and/or image quality and was included for novelty.…”
Section: Anthropomorphic Phantomsmentioning
confidence: 99%
“…A study reviewing radiology departments in Sao Paulo, Brazil, reported that head (skull and sinus) examinations are one of the three most frequent examinations performed at a rate of 47 per 1,000 population, and with a population of 39.2 million this accounts for 1.84 million people annually [20]. Given the more frequent usage in developing countries and its occasional usage in developed countries, every effort should be made to ensure that all cranial projections are optimized to keep the dose to the patient as low as reasonably achievable, particularly because some patients will most likely undergo subsequent computed tomographic imaging [16,17,21].…”
Section: Introductionmentioning
confidence: 99%